Thermal and Storage Characteristics of Biomass Briquettes with Organic Binders - Wakchaure, G C; MANI, INDRA (Journal of Agricultural Engineering, 2012)
The thermal and storage characteristics of briquettes made of three different biomasses using four different concentrations of organic binders as molasses, press mud and distillers dry grain were studied. The concentrations of the organic binders were 5, 10, 15 and 20 per cent. The biomass as mustard stalk, mixed waste of tree leaves and grasses (3:1) and wood waste grounded to 5 mm size were converted to briquettes using piston type briquetting machine having three different dies with inner diameter of 41.5, 42.5 and 43.5 mm at corresponding die pressures of 123.4, 117.7 and 112.3 MPa. The calorific values were higher for briquettes prepared using press mud, followed by those with distiller’s dry grain and molasses, as the former mainly depended upon biomass and amount of binders. Bulk density and calorific values decreased with increase in storage period for all types of briquettes. An overall reduction of 49% in bulk density and about 9% in calorific value was found during storage for a period of 180 days. However, all the briquettes remained stable. The briquettes prepared at highest die pressure of 123.4 MPa showed less variation in moisture content, bulk density, tumbling resistance, shattering resistance, resistance to water penetration, calorific values and ash content over the storage period of 180 days as compared to those prepared at the other two die pressures.